2021
DOI: 10.1152/physiolgenomics.00087.2020
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2, ACE2 expression, and systemic organ invasion

Abstract: A novel coronavirus disease, COVID-19, has created a global pandemic in 2020, posing an enormous challenge to healthcare systems and affected communities. COVID-19 is caused by Severe Acute Respiratory Syndrome (SARS)-CoronaVirus-2 (CoV-2) that manifests as bronchitis, pneumonia, or a severe respiratory illness. SARS-CoV-2 infects human cells via binding a "spike" protein on its surface to angiotensin-converting enzyme 2 (ACE2) within the host. ACE2 is crucial for maintaining tissue homeostasis and negatively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
115
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(133 citation statements)
references
References 88 publications
1
115
0
3
Order By: Relevance
“…It is suggested that classifying ACE2 organ distribution could be useful to understand SARS-CoV-2 pathogenesis [ 9 ]. ACE2 expression was detected in various organs such as the heart, lung, kidneys, oral cavity, brain, pancreas, gastrointestinal tract and brain [ 7 ]. Therefore, it is likely that organ vulnerability and severity of pathology depend on the level of ACE2 gene expression [ 7 , 9 , 58 ], aligning with the hypothesis that high ACE2 levels have been detected in both lungs and heart [ 9 , 16 , 59 ].…”
Section: Sars-cov-2 Infection Starts From Lungs and Involves Heartmentioning
confidence: 99%
See 3 more Smart Citations
“…It is suggested that classifying ACE2 organ distribution could be useful to understand SARS-CoV-2 pathogenesis [ 9 ]. ACE2 expression was detected in various organs such as the heart, lung, kidneys, oral cavity, brain, pancreas, gastrointestinal tract and brain [ 7 ]. Therefore, it is likely that organ vulnerability and severity of pathology depend on the level of ACE2 gene expression [ 7 , 9 , 58 ], aligning with the hypothesis that high ACE2 levels have been detected in both lungs and heart [ 9 , 16 , 59 ].…”
Section: Sars-cov-2 Infection Starts From Lungs and Involves Heartmentioning
confidence: 99%
“…ACE2 expression was detected in various organs such as the heart, lung, kidneys, oral cavity, brain, pancreas, gastrointestinal tract and brain [ 7 ]. Therefore, it is likely that organ vulnerability and severity of pathology depend on the level of ACE2 gene expression [ 7 , 9 , 58 ], aligning with the hypothesis that high ACE2 levels have been detected in both lungs and heart [ 9 , 16 , 59 ]. In addition, alveolar epithelial type II cells and cardiomyocytes (mostly aged ones) have high expression of genes that positively regulate viral reproduction and transmission thus, consistently with lung and heart vulnerability [ 22 , 60 ].…”
Section: Sars-cov-2 Infection Starts From Lungs and Involves Heartmentioning
confidence: 99%
See 2 more Smart Citations
“…J16012 and Ji408005 were only positive in respiratory tract tissues, Ji408005 tested positive in the pharyngeal mucosa, lung and two lung lymph nodes, while viral RNA was detected in the carinal part of the trachea, lung and four lung lymph nodes of animal J16012. In the two other PCR-positive macaques (R14002 and J16017), RNA was detected in the respiratory system and the tracheobronchial lymph nodes, but also in cervical and mesenteric lymph nodes, skin, conjunctiva, liver, spleen, kidney, salivary gland and heart, all organs and tissues that have been described as target tissues in humans [58]. High viral RNA loads were measured in some lymph nodes of these animals, ranging from 2 x 10 5 to 1 x 10 6 GE/gram of tissue.…”
Section: Resultsmentioning
confidence: 99%